Search for massive long-lived highly ionising particles with the ATLAS detector at the LHC - Anduaga, Xabier Sebastián (2011)
A search is made for massive highly ionising particles with lifetimes in excess of 100 ns, with the ATLAS experiment at the Large Hadron Collider, using 3.1 pb-1 of pp collision data taken at √s = 7TeV. The signature of energy loss in the ATLAS inner detector and electromagnetic calorimeter is used. No such particles are found and limits on the production cross section for electric charges 6e ≤ |q| ≤ 17e and masses 200 GeV ≤ m ≤ 1000 GeV are set in the range 1–12 pb for different hypotheses on the production mechanism.